Two pricing mechanisms in sponsored search advertising - Wei Yang; Youyi Feng; Baichun Xiao (Games, 2013)
Sponsored search advertising has grown rapidly since the last decade and is now a significant revenue source for search engines. To ameliorate revenues, search engines often set fixed or variable reserve price to in influence advertisers' bidding. This paper studies and compares two pricing mechanisms: the generalized second-price auction (GSP) where the winner at the last ad position pays the larger value between the highest losing bid and reserve price, and the GSP with a posted reserve price (APR) where the winner at the last position pays the reserve price. We show that if advertisers' per-click value has an increasing generalized failure rate, the search engine's revenue rate is quasi-concave and hence there exists an optimal reserve price under both mechanisms. While the number of advertisers and the number of ad positions have no effect on the selection of reserve price in GSP, the optimal reserve price is affected by both factors in APR and it should be set higher than GSP.
Keywords: 330; sponsored search advertising; symmetric Nash equilibrium; generalized failure rate; generalized second-price auction; reserve price